2019
DOI: 10.1111/jcmm.14612
|View full text |Cite
|
Sign up to set email alerts
|

Uridine phosphorylase 1 associates to biological and clinical significance in thyroid carcinoma cell lines

Abstract: Thyroid cancer incidence has been continuity increasing worldwide. Uridine phosphorylase 1 (UPP1) is a protein‐coding gene and has been detected that UPP1 was the higher expression in many solid malignancies, just as head and neck cancers, breast cancer, compared with paired normal tissue. But the act of UPP1 in thyroid cancer is not explicit. In this article, we investigate the function of UPP1 expression in thyroid cancer. The Cancer Genome Atlas (TCGA) unpaired thyroid cancer and normal RNA‐seq data were do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…The expression of METTL14 is decreased in HCC, especially in metastatic HCC [119] Pancreatic cancer METTL3 N.A. METTL3 protein, m 6 A abundance and mRNA levels are much higher in tumour specimens than in para-cancerous specimens [120] YTHDF2 YAP Increased YTHDF2 promotes proliferation and suppresses migration of pancreatic cancer by destabilizing YAP mRNA [121] Lung cancer METTL3 EGFR/ TAZ METTL3 enhances the translation of EGFR and TAZ mRNA in lung cancer [ [164] mRNA modifications that can change the structure of transcripts, and the other is mRNA modifications that can regulate transcription by joining hands with a complex of enzymes, such as METTL3 or NSUN2. Considering that modifications can regulate the fate of diverse diseases, such modifications have the potential to be utilized in targeted therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of METTL14 is decreased in HCC, especially in metastatic HCC [119] Pancreatic cancer METTL3 N.A. METTL3 protein, m 6 A abundance and mRNA levels are much higher in tumour specimens than in para-cancerous specimens [120] YTHDF2 YAP Increased YTHDF2 promotes proliferation and suppresses migration of pancreatic cancer by destabilizing YAP mRNA [121] Lung cancer METTL3 EGFR/ TAZ METTL3 enhances the translation of EGFR and TAZ mRNA in lung cancer [ [164] mRNA modifications that can change the structure of transcripts, and the other is mRNA modifications that can regulate transcription by joining hands with a complex of enzymes, such as METTL3 or NSUN2. Considering that modifications can regulate the fate of diverse diseases, such modifications have the potential to be utilized in targeted therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, uridine phosphorylase 1 (UPP1) is another enzyme that can reversibly catalyse the phosphorolysis of uridine to uracil [162,163]. It has been reported that expression of UPP1 significantly depends on lymph node metastasis and tumour stage and size in patients with thyroid carcinoma [164] (Table 3, Fig. 4).…”
Section: Aberrant Hm 5 C ψ I U and 2'-o-me Rna Modifications In Dimentioning
confidence: 99%
“…[ 32 ] Researches have investigated the connections between the expression of UPP1 and the prognosis of cancer patients. They demonstrated that the higher the level of UPP1 in the tumor, the worse the prognosis and the shorter the survival time of cancer patients [ 33 ]. But genes are not an isolated island, the interactions between genes form a beautiful pulsating map of life.…”
Section: Discussionmentioning
confidence: 99%
“…Researches have investigated the connections between the expression of UPP1 and the prognosis of cancer patients. They demonstrated that the higher the level of UPP1 in the tumor, the worse the prognosis and the shorter the survival time of cancer patients [31]. But genes are not an isolated island, the interactions between genes form a beautiful pulsating map of life.…”
Section: Discussionmentioning
confidence: 99%